2022
DOI: 10.1021/acsaem.2c00026
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the Heat Generation Power of a LiNi0.8Co0.1Mn0.1O2 Cathode by Coating with Reduced Graphene Oxide

Abstract: Heat generation, accumulation, and runaway severely affect the practical applications of lithium-ion batteries (LIBs) using Ni-rich Ni/Co/Mn ternary cathode materials. In principle, the aforementioned thermal characteristics of a LIB are mainly determined by the heat generation power of the cathode and anode materials during charging/discharging. In this work, the heat generation power of the LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM811) cathode material coated with and without reduced graphene oxide (rGO) is studied sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Predictably, increasing the cutoff voltage for charging should affect the heat generation power of NCM811. To elaborate the assumption, by coupling a calorimeter (TAM Air) with a LAND-CT2001A electrochemical workstation, 43 generation power is calculated following the equations proposed by Song et al, 22,44 and the results are summarized in Figure 1b. With the charging cutoff voltage increasing, the heat generation power increases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Predictably, increasing the cutoff voltage for charging should affect the heat generation power of NCM811. To elaborate the assumption, by coupling a calorimeter (TAM Air) with a LAND-CT2001A electrochemical workstation, 43 generation power is calculated following the equations proposed by Song et al, 22,44 and the results are summarized in Figure 1b. With the charging cutoff voltage increasing, the heat generation power increases.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we demonstrated that the particle size, electric conductivity, and lithium-ion diffusion coefficient of NCM811 could all affect its heat generation power during charge/discharge procedures. 43 Herein, these internal parameters of NCM811 before and after 205 cycles under charging cutoff voltages of 4.3, 4.5, and 4.8 V were also characterized. Figure S4 shows the FE-SEM image of NCM811 electrodes before and after 205 cycles under different charging cutoff voltages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protective particle coatings, mainly including metal oxides, [10][11][12][13] oxide solid electrolytes, [14][15][16] phosphates, [6,17,18] fluorides, [19][20][21][22] or graphene, [23][24][25] were widely utilized to address these problems. For example, Xu et al [26] used Al 2 O 3 and Zhou et al [10] utilized ZnO.…”
Section: Introductionmentioning
confidence: 99%